128k views
1 vote
What is the 13th term of the geometric sequence with this explicit formula?an-3-(-2)(n-1)

What is the 13th term of the geometric sequence with this explicit formula?an-3-(-2)(n-example-1
User Mynawaz
by
5.3k points

1 Answer

2 votes

Answer:

C. 12,288

Explanation:

Given the explicit formula of a given geometric sequence:


a_n=3(-2)^(n-1)

To find the 13th term, substitute n for 13:


\begin{gathered} a_(13)=3*(-2)^(13-1) \\ =3*(-2)^(12) \\ =3*4096 \\ =12,288 \end{gathered}

The 13th term of the geometric sequence is 12,288.

Option C is correct.

User Noir
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.